Overcoming cold tumors: a combination strategy of immune checkpoint inhibitors - Ouyang, Peng; Wang, Lijuan; Wu, Jianlong; Tian, Yao; Chen, Caiyun; Li, Dengsheng; Yao, Zengxi; Chen, Ruichang; Xiang, Guoan; Gong, Jin; Bao, Zhen (Frontiers in Immunology, 2024)
Immune Checkpoint Inhibitors (ICIs) therapy has advanced significantly in treating malignant tumors, though most ‘cold’ tumors show no response. This resistance mainly arises from the varied immune evasion mechanisms. Hence, understanding the transformation from ‘cold’ to ‘hot’ tumors is essential in developing effective cancer treatments. Furthermore, tumor immune profiling is critical, requiring a range of diagnostic techniques and biomarkers for evaluation. The success of immunotherapy relies on T cells’ ability to recognize and eliminate tumor cells. In ‘cold’ tumors, the absence of T cell infiltration leads to the ineffectiveness of ICI therapy. Addressing these challenges, especially the impairment in T cell activation and homing, is crucial to enhance ICI therapy’s efficacy. Concurrently, strategies to convert ‘cold’ tumors into ‘hot’ ones, including boosting T cell infiltration and adoptive therapies such as T cell-recruiting bispecific antibodies and Chimeric Antigen Receptor (CAR) T cells, are under extensive exploration. Thus, identifying key factors that impact tumor T cell infiltration is vital for creating effective treatments targeting ‘cold’ tumors.